Cervical musculoskeletal disorders and their relationships with personal and work-related factors among electronic assembly workers. (December 2019) - Maimaiti, Nazhakaiti; Wang, Jingjing; Jin, Xianning; Wang, Shijuan; Qin, Dongliang; He, Lihua; Wang, Fujiang; Zhang, Zhongbin; Forsman, Mikael; Yang, Liyun; Yang, Qiuyue; Wang, Haijiao
Highlights: Reporting of factors associated with neck pain among electronic workers in China. Comparison of findings from logistic regression and SEM. Variables' direct or indirect functional routes are proved. Abstract: Introduction: Electronics assembly workers are reported to have a high prevalence of musculoskeletal disorders (MSDs). This study investigated the prevalence of cervical MSDs and the complex relationships between cervical MSDs and individual, physical, psychosocial factors among electronics assembly workers. Methods: In this cross-sectional survey, self-administered questionnaires from 700 workers in electronics manufacturing workshops were analysed. Information concerning musculoskeletal symptoms, personal and work-related factors was collected. Finally, the prevalence of cervical MSDs was computed for different subgroups, and the relationships with different factors were analyzed using logistic regression and structural equation modeling (SEM). Results: The total 12 month prevalence of cervical MSDs among the survey population was 29.4%. Variables of gender, job tenure, twisting head frequently, neck flexion/extension for long time and work required to be done quickly showed significant associations with MSDs in a multivariate logistic regression ( P < 0.05). The SEM analysis showed moderate and significant correlations between postural load ( γ = 0.279), gender ( γ = 0.233) and cervical MSDs, while there were weak but significant correlations between vibration ( γ = 0.024), work stress ( γ = 0.126), job tenure ( γ = 0.024) and cervical MSDs. Both work stress and vibration affected the MSDs indirectly through postural load. Conclusions: The logistic regression results support previous general epidemiological MSD studies, and indicates that individual, physical, and psychosocial factors are related to cervical MSDs. The SEM provides a better approximation of the complexity of the relationship between risk factors and cervical MSDs. Improving awkward postures may be effective ways to control the influence of occupational stressors or vibration on MSDs. Practical Applications: The study is to improve prevention of MSDs among electronics assembly workers and promote their occupational health.